Cost analysis of the Philippine Legislative process - Aguja, Hilton J. (2009)
As the elections in 2010 approaches, issues involving charter change are hitting the headlines. In the main, all sides agree on the need of instituting changes in the Constitution. The only point of significant disagreement has to do with the timing and the mode by which such changes may be affected. The disagreement is borne by the fear of the opposition that changing the Constitution may be used as the Trojan horse by the administration to perpetuate President Arroyo in power. Partisanship aside, this paper joins in the discourse with a clear agenda. It argues for charter change from the standpoint of economy and simplicity. The present congressional set-up for legislation is redundant, cumbersome and circuitous. Also, it is very costly to maintain.
Keywords: Charter change